Ideologization of Hijrah in Social Media: Digital Activism, Religious Commodification, and Conservative Domination - Muhammad Iqbal Juliansyahzen (Millah: Journal of Religious Studies, 2023)
This paper studies the development of the movement and the meaning of hijrah in social media. Hijrah was originally understood as a process of leaving the past misguidance (jahiliyyah) and towards conditions that are in accordance with syariat. In its development, hijrah refers to a transformation of individuals who are less religious to more religious (Islamī). The form of this transformation can be seen from the choice of clothes, work preferences, and social relations models. The ideological process of the meaning of hijrah was carried out massively through social media. This is based on the search results on the internet about “hijrah” is more than other religious topics. This article answers how and why hijrah is interpreted and articulated by several digital activists. This research is qualitative research with a critical discourse analysis method combined with a digital hermeneutic approach. Based on research, digital activists who carry out the ideologization of the meaning of hijrah are preachers who have many followers on social media. Followers on social media are capital and modal in mainstreaming a discourse and idea. This article reveals that religious studies regarding hijrah on social media are not only related to understanding religious texts but are also part of religious commodification. In addition, the dominance of conservative groups is a fact that cannot be separated from the ideological flow of hijrah on social media.